IgG autoantibodies in bullous pemphigoid induce a pathogenic MyD88-dependent pro-inflammatory response in keratinocytes - Lei Bao; Christian F. Guerrero-Juarez; Jing Li; Manuela Pigors; Shirin Emtenani; Yingzi Liu; Adrian P. Mansini; Yulu F. Wang; Aadil Ahmed; Norito Ishii; Takashi Hashimoto; Bethany E. Perez White; et al. (Nature Communications)
Abstract Autoantibodies in bullous pemphigoid (BP) are known to activate the innate immune response. Nevertheless, the direct effect of autoantibodies on keratinocytes and the contribution of keratinocyte responses to the pathology of BP are largely unknown. Here, by performing multiplex immunoassays and RNA-seq on primary keratinocytes treated with IgG derived from BP patients, we identify a MyD88-dependent pro-inflammatory and proteolytic response characterized by the release of several cytokines (IL-6, IL-24, TGF-β1), chemokines (CXCL16, MIP-3β, RANTES), C1s, DPP4, and MMP-9. The activation of this MyD88-dependent response is further validated using spatial transcriptomics and scRNA-seq of diseased skin. Blistering of the skin appears to significantly impact this inflammatory response, with attached BP skin and spongiotic dermatitis revealing indistinguishable transcriptomes. In a preclinical mouse model of BP, Krt14-specific Myd88 knockout significantly decreases disease severity and reduces serum levels of IL-4 and IL-9, indicating a contributory role of keratinocyte-derived skin inflammation in the systemic response. Thus, our work highlights key contributions of keratinocytes in response to autoantibodies in BP.